Implementação de Ipv6 em uma rede local virtualizada - Carvalho, Luis Henrique (2015)
This monograph was developed through a literature research for articles, books, monographs already published and in the case study of the implementation of IPv6 in a virtualized network in GNS3. This activity is practiced in the walkthrough for emulation two remote lans interconnected through their routers, thus forming a WAN with IPv4. After that, step by step appears to configure the IPv6 communication with dynamic routing via CISCO RIPng protocol.